Les trames vertes urbaines, un nouveau support pour une cité verte ? - Jean-Michel Le Bot; Françoise Philip (Développement Durable et Territoires)
Urban green frames, a new basis for a green city ? In 1993, Lafaye and Thevenot put forward the hypothesis of a seventh “order of worth” – which has been called the “green city” – besides the six other “orders of worth” identified by Boltanski and Thévenot. Based on semi-directive interviews with public officers and members of non-governmental organizations engaged in the debates about urban green frames of three metropolitan areas in the West of France (Angers, Nantes and Rennes), the current paper shows that, after nearly 20 years, urban green frames take their justification principles from the six pre-existing “orders of worth”. Although “Grenelle 2” French regulation, which defines the green and blue frames, emphasizes the necessity to protect biodiversity for itself, green frames local developers are willing to translate this necessity and achieving compromises between worlds.